Writers' mistakes a handbook of common blunders and ways to mend them - Olmsted, Franklin B. (Rowman & Littlefield, 2024)
"Writers Mistakes: A Handbook of Common Blunders and Ways to Mend Them is a comprehensive guide where readers will find hints on how to avoid certain words, phrases, and common mistakes that can obscure the messages of ones work"-- Provided by publisher.